Dietary Supplement Ingredient Database (DSID) and the Application of Analytically Based Estimates of Ingredient Amount to Intake Calculations. (3rd August 2018) - Andrews, Karen W; Gusev, Pavel A; McNeal, Malikah; Savarala, Sushma; Dang, Phuong Tan V; Oh, Laura; Atkinson, Renata; Pehrsson, Pamela R; Dwyer, Johanna T; Saldanha, Leila G; Betz, Joseph M; Costello, Rebecca B; et al.
Abstract: Objective: We describe the purpose of the Dietary Supplement Ingredient Database (DSID), the statistical methodology underlying online calculators of analytically verified supplement content estimates, and the application and significance of DSID label adjustments in nutritional epidemiology. Background and History: During dietary supplement (DS) manufacturing, many ingredients are added at higher than declared label amounts, but overages are not standardized among manufacturers. As a result, researchers may underestimate nutrient intakes from DSs. The DSID provides statistical tools on the basis of the results of chemical analysis to convert label claims into analytically predicted ingredient amounts. These adjustments to labels are linked to DS products reported in NHANES. Rationale: Tables summarizing the numbers of NHANES DS products with ingredient overages and below label content show the importance of DSID adjustments to labels for accurate intake calculations. Recent Developments: We show the differences between analytically based estimates and labeled content for vitamin D, calcium, iodine, caffeine, and omega-3 (n–3) fatty acids and their potential impact on the accuracy of intake assessments in large surveys. Analytical overages >20% of label levels are predicted for several nutrients in 50–99% of multivitamin-mineral products (MVMs) reported in NHANES: for iodine and selenium in adult MVMs, for iodine and vitamins D and E in children's MVMs, and for iodine, chromium, and potassium in nonprescription prenatal MVMs. Predicted overages of 10–20% for calcium can be applied to most MVMs and overages >10% for folic acid in the vast majority of adult and children's MVMs. Future Directions: DSID studies are currently evaluating ingredient levels in prescription prenatal MVMs and levels of constituents in botanical DSs. Conclusions: We estimate that the majority of MVM products reported in NHANES have significant overages for several ingredients. It is important to account for nonlabeled additional nutrient exposure from DSs to better evaluate nutritional status in the United States.